(untitled) (Eurasian Journal of History, Geography and Economics, 2022)
The Iraqi economy witnessed an openness after 2004, and this would place the responsibility on local production to keep pace with international economic developments, and mobilize the energies of the economy towards increasing production and achieving economic surplus, by supporting exports, and to develop a platform that determines its imports from the inputs of the production process in line with local capabilities On the other hand, to provide these materials and maintain competitiveness. But what happened after 2004 was random steps without proper economic planning, which led to a distortion of the process of economic openness, which caused the Iraqi economy to lose its economic resources and production capacities. The research assumes that exports and imports can be harnessed to serve sustainable economic development plans and to achieve an economic surplus when there is a real will on the part of decision makers to build their economy and face its problems. The research concluded weak economic indicators related to the activity of exports and imports, and the predominance of the rentier economy. Iraq has lost its economic resources and the inability to implement sustainable economic development plans. The research recommended that the decision-makers’ will is important in overcoming the difficulties and obstacles that stand behind the distortion of the structure of the Iraqi economy, and not benefiting from exports and imports in mobilizing the capabilities of the local economy.